Extracellular proteases produced by marine bacteria isolated from sea water contaminated with fishing effluents - Sánchez, Tito (2004)
A total of 26 strains of marine bacteria with proteolytic activity was isolated from sea water contaminated with fishing effluents; they were evaluated in basis of their growth and formation of activity halos in Marine Agar supplemented with casein to 1%, pH 8,0 and incubated to 25 ºC per 72 hours. Selected five strains were evaluated on the basis of displaying the best halos of activity as well by their growth and production of proteases at different concentrations of NaCl, temperature ranges and pH; being finally considered as moderate halotolerants bacteria, psicrotrophics and alkalophile. These strains also were evaluated by their specific proteolytic activity on the casein, being strain CM48 (Pseudomonas sp.) the one that presented the best specific activity (17,38 U/mg) at 72 hours, and followed by strain CM45 (Alcaligenes sp.) (12,09 U/mg) and three strains of Aeromonas sp. (CM43, CM44 and CM46) with values of 12,02; 10,07 and 10,10 U/mg respectively.